The History of the Development of Geodetic Works in Engineering Fields - Karimov Faxriddin Alievich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Engineering geodesy functions as the spatial foundation for all complex infrastructure projects, evolving from basic analog mensuration to sophisticated multidimensional spatial data management. This investigation chronologically and quantitatively evaluates the technological paradigm shifts within applied engineering surveying over the past century. By conducting a systematic comparative analysis of 85 major civil and industrial engineering projects executed between 1950 and 2025, the research tracks the precise correlation between instrument innovation and structural tolerance limits. Methodological approaches incorporated retrospective error analysis, shifting from optical-mechanical theodolite networks to contemporary Global Navigation Satellite Systems (GNSS) and Light Detection and Ranging (LiDAR) integrations. The empirical data indicates a profound geometric accuracy transformation; acceptable deviation margins in bridge and tunnel construction plummeted from ±18.5 mm in the 1960s to an ultra-precise ±1.2 mm in recent Building Information Modeling (BIM) environments. Furthermore, field productivity metrics demonstrate an 840% efficiency acceleration resulting from Unmanned Aerial Vehicle (UAV) photogrammetry compared to classical terrestrial triangulation. The transition toward real-time structural health monitoring networks fundamentally redefines the surveyor’s operational scope. The study empirically substantiates that modern geodetic engineering no longer merely maps pre-existing terrain but actively dictates the geometric viability and lifecycle sustainability of advanced architectural forms.